Open Source and Closed Source Software Development Methodologies - Potdar, Vidyasagar; Chang, Elizabeth (IEE The Institution of the Electrical Engineers, 2004)
Open source software development represents a fundamentally new concept in the field of software engineering. Open source development and delivery occurs over the Internet. Developers are not confined to a geographic area. They work voluntarily on a project of their choice. As new requirements emerge, the software is enhanced bv the user/developers. In this paper we show a comparative study of open source and closed source software development approaches and present a software life cycle model for open source software development.